Biocompatible chitosan-modified core-shell Fe3O4 nanocomposites for exigent removal of blood lactic acid. (19th June 2020) - Yang, Lingyi; Wang, Wenhong; Hu, Yufeng; Guo, Jing; Huang, Xiao
Abstract: Excess lactic acid in blood will lead to hyperlactatemia, which is frequently detected in critically ill patients admitted to the intensive care. Reducing the blood lactic acid content using acute treatments becomes particularly important for bringing a patient out of danger. Traditional treatments often fail in case of malfunctioning of a patients' metabolism. Herein, nanotechnology was introduced to remove blood lactic acid independent of metabolism. In this work, chitosan was employed as the shell to adsorb lactic acid, and Fe3 O4 nanoparticles were employed as the core to enable proper magnetic separation property. Our data showed that core–shell nanocomposites (NCs) had an exigent and efficient adsorption behavior. Furthermore, they could be easily separated from blood plasma by magnetic separation. Thus, the good hemocompatibility and cytocompatibility indicated that of core–shell NCs hold great potential in lactic acid removal for emergent hyperlactatemia treatment.